Respuesta :
First we need to combine like terms:
-18 + 15x = 12x - 18 + 3x
-18 + 15x = 9x - 18
-18 = 9x - 18 - 15x
-18 = -6x - 18
0 = -6x (the 18's cancel)
0 / -6 = x
0 = x
-18 + 15x = 12x - 18 + 3x
-18 + 15x = 9x - 18
-18 = 9x - 18 - 15x
-18 = -6x - 18
0 = -6x (the 18's cancel)
0 / -6 = x
0 = x
-18 + 15x = 3(4x - 6) + 3x; 3 × 4x= 12x; 3 × -6= -18; -18 + 15x = 12x - 18 + 3x; 12x + 3x= 15x; -18 + 15x = 15x - 18;
The answer is infinite solution.
Hope this helps :)
The answer is infinite solution.
Hope this helps :)